VERTEX EXPONENTS OF A CLASS OF TWO-COLORED HAMILTONIAN DIGRAPHS - Syahmarani, Aghni; Suwilo, Saib (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI :Â http://dx.doi.org/10.22342/jims.18.1.105.1-19